Your answer is incorrect. You forgot to get the square root of 25 and 4. Answer should be 16√2
we can only subtract radicals that are the same. At first glance, 4√50 - 2√8 are not the same, so they are not likely to be subtracted. However, each radical can still be simplified.
4 √50 = 4 √25 * 2 = 4 * 5 √2 = 20 √2
2 √8 = 2 √4 * 2 = 2 * 2 √2 = 4 √2
Now that the radicals are the same. then you can subtract the numbers.
20 √2 - 4 √2 = 16√2
3y = 6
Product means multiply so 3 multiplied by y is 3y which is equal to 6. :)
Answer:
rate of change
Step-by-step explanation:
Answer:
option A
Step-by-step explanation:
given coordinate (3, -6) and (–7, –4)
to find the equation of line
slope of the line passing through both the point will be
![m = \dfrac{y_2-y_1}{x_2-x_1}](https://tex.z-dn.net/?f=m%20%3D%20%5Cdfrac%7By_2-y_1%7D%7Bx_2-x_1%7D)
![m = \dfrac{-4+6}{-7-3}](https://tex.z-dn.net/?f=m%20%3D%20%5Cdfrac%7B-4%2B6%7D%7B-7-3%7D)
![m = -\dfrac{2}{10}](https://tex.z-dn.net/?f=m%20%3D%20-%5Cdfrac%7B2%7D%7B10%7D)
equation of line
( y - y₁ ) = m ( x - x₁ )
![y + 6= -\dfrac{2}{10}(x - 3)](https://tex.z-dn.net/?f=y%20%2B%206%3D%20-%5Cdfrac%7B2%7D%7B10%7D%28x%20-%203%29)
x + 5 y = -27
line which will not intersect will be parallel to it so option A has same slope as our line equation i.e. -1/5
hence, correct answer is option A
<h2>
Answer:</h2>
The values of x for which the given vectors are basis for R³ is:
![x\neq 1](https://tex.z-dn.net/?f=x%5Cneq%201)
<h2>
Step-by-step explanation:</h2>
We know that for a set of vectors are linearly independent if the matrix formed by these set of vectors is non-singular i.e. the determinant of the matrix formed by these vectors is non-zero.
We are given three vectors as:
(-1,0,-1), (2,1,2), (1,1, x)
The matrix formed by these vectors is:
![\left[\begin{array}{ccc}-1&2&1\\0&1&1\\-1&2&x\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D-1%262%261%5C%5C0%261%261%5C%5C-1%262%26x%5Cend%7Barray%7D%5Cright%5D)
Now, the determinant of this matrix is:
![\begin{vmatrix}-1 &2 & 1\\ 0& 1 & 1\\ -1 & 2 & x\end{vmatrix}=-1(x-2)-2(1)+1\\\\\\\begin{vmatrix}-1 &2 & 1\\ 0& 1 & 1\\ -1 & 2 & x\end{vmatrix}=-x+2-2+1\\\\\\\begin{vmatrix}-1 &2 & 1\\ 0& 1 & 1\\ -1 & 2 & x\end{vmatrix}=-x+1](https://tex.z-dn.net/?f=%5Cbegin%7Bvmatrix%7D-1%20%262%20%26%201%5C%5C%200%26%201%20%26%201%5C%5C%20-1%20%26%202%20%26%20x%5Cend%7Bvmatrix%7D%3D-1%28x-2%29-2%281%29%2B1%5C%5C%5C%5C%5C%5C%5Cbegin%7Bvmatrix%7D-1%20%262%20%26%201%5C%5C%200%26%201%20%26%201%5C%5C%20-1%20%26%202%20%26%20x%5Cend%7Bvmatrix%7D%3D-x%2B2-2%2B1%5C%5C%5C%5C%5C%5C%5Cbegin%7Bvmatrix%7D-1%20%262%20%26%201%5C%5C%200%26%201%20%26%201%5C%5C%20-1%20%26%202%20%26%20x%5Cend%7Bvmatrix%7D%3D-x%2B1)
Hence,
![-x+1\neq 0\\\\\\i.e.\\\\\\x\neq 1](https://tex.z-dn.net/?f=-x%2B1%5Cneq%200%5C%5C%5C%5C%5C%5Ci.e.%5C%5C%5C%5C%5C%5Cx%5Cneq%201)